SOSIALISASI PENGAWASAN PARTISIPATIF PEMILU 2024 BERDASARKAN PERBAWASLU NO 2 TAHUN 2023 BAGI PEMUDA KELURAHAN INDUSTRI TENAYAN - ,; ,; ,; , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
The partner's problem is that the youth of the Tenayan Industrial sub-district, who are a strategic part of the community, do not know and understand the importance of participation in election supervision so that they are of higher quality. The target of community service activities is to increase knowledge and understanding of the importance of participation in election supervision so that they are of higher quality. Solutions agreed upon by the proposing team and partners to address priority issues need to be socialized in the form of counseling and face-to-face discussions. The method of implementing lectures, delivering material, on this occasion the participants were free to ask and answer. The details of this method are, 1. Submission of material, 2. Interactive dialogue, this dialogue serves as brainstorming from participants to obtain input in the form of problems, aspirations, suggestions, ideas and solutions. Partner participation provides time and mobilizes youth participants with both student and student status as the target audience. The output is expected to increase knowledge, understand the target audience of the importance of participatory oversight of the 2024 election, for those proposing the output achieved is in the form of a scientific article.